Antibiotic consumption in 14 countries of sub-Saharan Africa: Findings from a retrospective analysis - Yvon de Jong; Rachit Singhal; Yewande Alimi; Geetanjali Kapoor; Abdourahmane Sow; Martin Matu; Edwin Shumba; Manuel Moreira; Deepak Batra; Ramanan Laxminarayan; Pascale Ondoa (PLoS ONE, 2025)
Background Antimicrobial consumption (AMC) measures the level and types of antibiotics consumed in a specific setting. Monitoring AMC is critical component of antimicrobial resistance (AMR) containment strategies. However, AMC data at both facility and national-levels are scarce in Africa, which limits our understanding of the rate, patterns and drivers of antibiotic consumption, and prevents the establishment of evidence-based antimicrobial stewardship. Methods We determined facility and national-level rates and patterns of AMC from data retrospectively collected between 2016 and 2019 in 327 pharmacies from 14 countries AMC data collection followed a backfilling strategy leveraging from public and private central medical stores, wholesalers, distributors or import services as data sources. Participating hospital and community pharmacies were selected based on their location in or proximity to hospitals capable of producing AMR data. Levels of AMC were determined as defined daily dose (DDD) and DDD per inhabitant (DID). AMC patterns were analysed according to the WHO Access, Watch, and Reserve (AWaRe) Categories, the Anatomical Therapeutic Chemical (ATC) classes and the individual antibiotic molecules included in the Drug Utilisation 75% (DU75). The availability of antibiotics was examined against the WHO and the National Essential Medicine Lists (EML). Results National AMC data was available in 11 of the 14 participating countries, revealing a collective AMC of 8.42 DID varying from 2.8 to 115.5 at individual country level. AMC was also determined in 327 hospital and community pharmacies. Nine of 11 (82%) countries with national data available, and 219 of the 327 (72%) participating pharmacies achieved the WHO AWaRe target of at least 60% of antibiotic consumption from Access drugs. Eighty percent of country-level AMC was accounted for by five ATC sub-classes classes of antibacterial for systemic use. Facility-level antibiotic consumption was dominated by a narrow scope of less than five drugs, taking advantage of only 10% of all possible WHO-recommended Access drugs within ATC classes. Collectively, the 14 national EML included 70% of Access, 60% of Watch and less than 5% of Reserve antibiotics listed in the WHO EML. Forty-eight uncategorized and 50 categorized non-WHO-recommended drugs were included in national EMLs or documented to be circulating in countries. Interpretation The relatively low AMC and the poorly diversified subset of antibiotics available in countries underscores that strategies to expand equitable access to adequate treatment of bacterial infections should complement current efforts to promote the judicious use of antimicrobials. Interventions to increase the volume of analysable data on AMU, AMC and AMR, should be prioritized in national AMR action plans as well as in wider infrastructural and economic development plans.